2021
DOI: 10.3390/ijms22168904
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of Prolactin-Releasing Peptide Increased Affinity for and Activation of the GPR10, NPFF-R2 and NPFF-R1 Receptors: In Vitro Study

Abstract: The anorexigenic neuropeptide prolactin-releasing peptide (PrRP) is involved in the regulation of food intake and energy expenditure. Lipidization of PrRP stabilizes the peptide, facilitates central effect after peripheral administration and increases its affinity for its receptor, GPR10, and for the neuropeptide FF (NPFF) receptor NPFF-R2. The two most potent palmitoylated analogs with anorectic effects in mice, palm11-PrRP31 and palm-PrRP31, were studied in vitro to determine their agonist/antagonist propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 45 publications
0
14
0
5
Order By: Relevance
“…Oxytocin neurons also express NPFFR [ 47 ], which couples to Gs and Gi as well as to Gq [ 24 , 48 , 49 ]. NPFFR activation stimulates cAMP production in olfactory bulb neurons [ 50 ] and increases phosphorylation of cAMP response element-binding protein (CREB) and c-Jun N terminal kinase (JNK) as well as activating c-Jun [ 19 ]. Hence, NPFFR-CREB/JNK signalling might mediate the direct effects of kisspeptin on oxytocin neurons in late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin neurons also express NPFFR [ 47 ], which couples to Gs and Gi as well as to Gq [ 24 , 48 , 49 ]. NPFFR activation stimulates cAMP production in olfactory bulb neurons [ 50 ] and increases phosphorylation of cAMP response element-binding protein (CREB) and c-Jun N terminal kinase (JNK) as well as activating c-Jun [ 19 ]. Hence, NPFFR-CREB/JNK signalling might mediate the direct effects of kisspeptin on oxytocin neurons in late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, Kiss1R activation increases phosphorylation of extracellular regulated kinase 1/2 (ERK1/2) [ 10 , 12 , 13 , 14 , 15 ] but also increases phosphorylation of p38 in some cell lines [ 13 , 14 ]. Similarly to Kiss1R, NPFFR activation also increases phosphorylation of ERK1/2 [ 16 , 17 , 18 , 19 ] and p38 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, SON Kiss1R mRNA expression does not change during pregnancy (Seymour et al 2017), suggesting that upregulation of Kiss1R does not underpin kisspeptin excitation of oxytocin neurons in late pregnancy, although the possibility of increased Kiss1R surface expression and/or sensitivity cannot be discounted. Oxytocin neurons also express NPFFR (Kim et al 2016), which couples to Gs and Gi as well as to Gq (Bonini et al 2000;Liu et al 2001;Mollereau et al 2002) to increase phosphorylation of cAMP response element-binding protein (CREB) and c-Jun N terminal kinase (JNK) (Karnosova et al 2021). Hence, NPFFR-CREB/JNK signalling might mediate the direct effects of kisspeptin on oxytocin neurons in late pregnancy.…”
Section: Local Kisspeptin Activation Of Oxytocin Neurons In Late Preg...mentioning
confidence: 99%
“…Classically, Kiss1R activation increases phosphorylation of extracellular regulated kinase 1/2 (ERK1/2) (Kotani et al 2001;Ohtaki et al 2001; Masui et al 2004; Kim et al 2010;Peng et al 2013) but also increases phosphorylation of p38 in some cell lines (Masui et al 2004; Kim et al 2010). Similarly to Kiss1R, NPFFR activation also increases phosphorylation of ERK1/2 (Anko and Panula 2006;Sun et al 2012;Yu et al 2016; Karnosova et al 2021) and p38 (Karnosova et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these disadvantages, we designed analogs of PrRP lipidized at the N-terminal region, which is not essential for biological activity (Maletínská et al, 2015;Kunes et al, 2016). Our earlier studies demonstrated that analogs lipidized by 8-18 carbon chain fatty acids at the N-terminus of PrRP20 or PrRP31 showed high binding affinities with a K i in the nanomolar range for both GPR10 and the NPFF2 receptor, similar to analogs that were palmitoylated through linkers to Lys 11 (e.g., palm 11 -PrRP31) (Maletínská et al, 2015;Pražienková et al, 2017;Karnošová et al, 2021).…”
Section: Introductionmentioning
confidence: 99%